THE HOLY AND GREAT COUNCIL IN THE CONTEXT OF SYNODALITY OF THE CHURCH–CANONICAL AND ECUMENICAL PERSPECTIVE - Đukić, Dalibor B; Kisić, Rade (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Preparations for the Holy and Great Council of the Orthodox Church, which was held in Crete in 2016, represent a modern expression of the institution of synodality. The authors made a comparative review of canonical and ecumenical perspectives of this institution with the aim of identifying similarities and differences in the conciliar consciousness of the Church. The first part of the paper points out the exceptional flexibility of this institution, which easily adapts to different church needs and social circumstances, as well as the fact that the conciliarity is the basic institution that forms the church organization from the parish to the universal level. The second part of the paper presents the pre-conciliar conferences and the issues they faced. The general conclusion of the paper is that the institution of synodality in the Orthodox Church has surpassed its canonical significance, which will always be unquestionable, and that it has gained its ecumenical perspective, thus becoming a factor of modern inter-church and inter-religious relations.